Postnatal cerebellar development in preterms with postconceptional age at term equivalent. A neuropathological study - Jones, Marta (2008)
To evaluate postnatal development, we analyzed 65 cerebella from preterm neonates at term-gestational-age equivalent, separated into 2 groups: Group I (GI), cerebellar weight (cw) up to 14 g; Group II (GII), cw more than 14 g. The control group (CG) consisted of 20 term neonates up to 6 days old. Morphometry showed: diminished size, expressed as a coefficient (GI: 2.2; GII:2.9; CG:3.68) and cw [g] (GI:9.8; GII:17.9; CG:26.71); in the lobes, diminished foliar height [μm] (inferior folia; GI: 3.486; GII:4.764; CG:6.458) and foliation; diminished cortical width [μm] (GI:63.9; GII:74.5; CG:92.27), and a high number of Purkinje cells per segment (GI:33.6; GII:21.4; CG:13.95). These results correlated significantly with each other, with brain weight, and to a lesser degree with body weight. No high correlation with gestational age was found. Brain lesions and different serious and protracted illnesses were more frequent in GI. Histology: necrosis and apoptosis of the immature cerebellar cortex as well as reactive astrocytosis and gliosis of the white matter were observed. These findings related to hypoxia-ischemia, infections, and therapies. In summary, the cases examined in this study evinced cerebellar patterns similar to those of 30-32 (GI) and 33-35 (GII) weeks of gestational age, although these preterm neonates had completed a postconceptional age of 37 to 42 weeks. These findings may be interpreted as having resulted from the action of noxa during the cerebellar lobes' vulnerability window. Direct injury of cerebellar cortex and white matter is a fundamental and poorly recognized cause of impaired cerebellar growth.